Bound States in the Continuum in Whispering Gallery Resonators - Retamal-Abarzua, J (American Physical Society, 2018)
We report the formation of bound states in the continuum in a whispering gallery resonator coupled to a one-dimensional waveguide. We find that an incident photon wave packet is partially stored in the bound state in the continuum due to a roughness-induced symmetry breaking. We discuss quantum interference effects such as Fano in the transmission spectra and the photonic density of states. The conditions under which the bound state can be accessed through single-photon transport processes are investigated. © 2018 American Physical Society.